2018
DOI: 10.1371/journal.ppat.1006872
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B aggravates coxsackievirus B3-induced myocarditis through activating the inflammasome and promoting pyroptosis

Abstract: Cathepsin B (CatB) is a cysteine proteolytic enzyme widely expressed in various cells and mainly located in the lysosomes. It contributes to the pathogenesis and development of many diseases. However, the role of CatB in viral myocarditis (VMC) has never been elucidated. Here we generated the VMC model by intraperitoneal injection of coxsackievirus B3 (CVB3) into mice. At day 7 and day 28, we found CatB was significantly activated in hearts from VMC mice. Compared with the wild-type mice receiving equal amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 50 publications
1
55
0
Order By: Relevance
“…One possibility is that enzymes, such as metalloproteinases and/or cathepsins, secreted during inflammation or released by cells undergoing cytolysis/necrosis may be responsible for the cleavage of pro-IL-1β in the extracellular milieu as described in other experimental models ( 75 77 ). Interestingly, in an animal model of viral myocarditis mice deficient in CTSB showed improved survival, reduced inflammatory cell tissue infiltration, and reduced IL-1β production, suggesting the CTSB aggravates the disease through activating the inflammasome-dependent IL-1β production and promoting pyroptosis ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that enzymes, such as metalloproteinases and/or cathepsins, secreted during inflammation or released by cells undergoing cytolysis/necrosis may be responsible for the cleavage of pro-IL-1β in the extracellular milieu as described in other experimental models ( 75 77 ). Interestingly, in an animal model of viral myocarditis mice deficient in CTSB showed improved survival, reduced inflammatory cell tissue infiltration, and reduced IL-1β production, suggesting the CTSB aggravates the disease through activating the inflammasome-dependent IL-1β production and promoting pyroptosis ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins trigger the prion‐like assembly of the inflammasome adaptor ASC into a pyroptosome, a filamentous helical structure that recruits caspase‐1, leading to the maturation of IL‐1β‐family cytokines and gasdermin‐D, and consequent release of cytokines into the extracellular space . Cholesterol crystals, protein aggregates such as β‐amyloid, and bacterial products disrupt lysosomal integrity and activate the NRLP3 inflammasome, inducing cytokine release and cell death . Interestingly, in most of these settings, cathepsin inhibition by genetic or pharmacological means blocks inflammasome activation and cell death .…”
Section: Lysosomes and Lmp In Other Cell Death Modalitiesmentioning
confidence: 99%
“…Cholesterol crystals, protein aggregates such as β‐amyloid, and bacterial products disrupt lysosomal integrity and activate the NRLP3 inflammasome, inducing cytokine release and cell death . Interestingly, in most of these settings, cathepsin inhibition by genetic or pharmacological means blocks inflammasome activation and cell death . Recent data also show that ASC specks can be released outside the cell during inflammasome‐mediated cell death.…”
Section: Lysosomes and Lmp In Other Cell Death Modalitiesmentioning
confidence: 99%
“…35 CVB3, as has been demonstrated by many epidemiological studies, is the most common pathogen for viral myocarditis. 33,36 Although the regulatory mechanisms underlying CVB3-induced dilated cardiomyopathy are still poorly dened, accumulating evidences suggest that the main pathologic factor of viral myocarditis is overwhelming inammation. 36 Importantly, it has been demonstrated that NLRP3 inammasome activation induced by CVB3 infection is a central player in developing myocardial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…33,36 Although the regulatory mechanisms underlying CVB3-induced dilated cardiomyopathy are still poorly dened, accumulating evidences suggest that the main pathologic factor of viral myocarditis is overwhelming inammation. 36 Importantly, it has been demonstrated that NLRP3 inammasome activation induced by CVB3 infection is a central player in developing myocardial dysfunction. 37 In this case, inhibition of NLRP3 inammasome activation is suggested as the most promising strategy for alleviating CVB3-induced myocardial damage.…”
Section: Discussionmentioning
confidence: 99%